If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3(k + -0.2) = 0.6 Reorder the terms: 0.3(-0.2 + k) = 0.6 (-0.2 * 0.3 + k * 0.3) = 0.6 (-0.06 + 0.3k) = 0.6 Solving -0.06 + 0.3k = 0.6 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '0.06' to each side of the equation. -0.06 + 0.06 + 0.3k = 0.6 + 0.06 Combine like terms: -0.06 + 0.06 = 0.00 0.00 + 0.3k = 0.6 + 0.06 0.3k = 0.6 + 0.06 Combine like terms: 0.6 + 0.06 = 0.66 0.3k = 0.66 Divide each side by '0.3'. k = 2.2 Simplifying k = 2.2
| 5x^2-4x-2=0 | | 12+3x=x | | 8x^3+6x^2-5x+1=0 | | 140-7x=29x+16 | | 2x-9=x | | -3x-1-5x+4= | | t^2=3t+7 | | 9-7x=108-28x | | 9-2x=x | | 6+5x=x | | x-2(x-1)=4-3(x-2) | | 13-8z=7 | | 12+5=11+12x | | -3(x-7)+2= | | 9(2-a)=63 | | 3(2+5m)=-54 | | 17(x-2)=34 | | 17(x-2)= | | 10-2(x+3)=3+3(2x+5) | | 4b-(9b-8)= | | 3x^2+10x+5=0 | | 379.94=3.14*r^2 | | 4+45=8x+13 | | 2x-5x=x+8 | | 4x+10=2x+29 | | -7y-(2y+4)= | | 4x^2+13=3 | | 2x^2=162 | | 5-4(x+1)=4x-3(4x-1)-4 | | 9+3b=18 | | 9+3b=15 | | 75.36=2r*3.14 |